Collective Housing and Residential Quality—Four Complexes of Low, Medium and High Density in Córdoba, Argentina - Marengo, Maria Cecilia (2019)
The study addresses an evaluation of the habitability conditions in collective housing from the perspective of building density and residential quality. The methodological proposal considered a multivariate approach. Initially, a simulation model was formulated integrating different situations in a residential quality index (density, scale, number of inhabitants). In this phase, a qualitative approach was incorporated to account for the perception of the inhabitants. The research question is: How density values are translated into satisfaction/dissatisfaction with a residential model? Four housing complexes of low, medium and high density, of public production in Córdoba city, Argentina are reinterpreted in light of the qualitative analysis, based on the development of interviews with key informants and observationson-site. The conclusion of the study allows new openings in the discussion of density values and residential quality, useful when planning housing interventions.